Initial progress to establish flying qualities requirements for maritime unmanned aircraft systems - Fell, T.R.; Jump, M.; White, M.D.; Owen, I. (My University, 2014)
This paper describes the development work being undertaken to establish Flying Qualities Requirements for Unmanned Aircraft Systems (UAS) expected to operate in the Maritime Environment. A UAS Dynamics Model (UDM) has been developed to allow the rapid investigation of the aircraft dynamics required to conduct ship-deck launch and recovery operations. The process used to develop the UDM is described. A typical recovery manoeuvre has been broken down into individual Mission Task Elements. These form the basis for the evaluation of the UDM dynamic responses against task-specific performance criteria. Two stochastic turbulence modelling schemes, the Control Equivalent Turbulence Inputs and Virtual AirDyn methods, have also been developed using previously computed time-accurate air wakes. These air wakes have been integrated into FLIGHTLAB modelling software and extracted using stochastic methods before integration into the UDM modelling environment. The model has been initially configured to assess an SH-60B-class UAS operating from a Type 23 Frigate.